A Systematic Review of Literature on Organizational Unlearning and Forgetting - LIAQUAT, MALKA; HASSAN, MUHAMMAD (The journal of contemporary issues in business and government, 2021)
Purpose – Unlearning has been one of the interesting and debatable construct emerged in studies of organizational behaviour. Discussion on this phenomenon precedes from interdisciplinary realms ranging from psychology to pedagogy approaching towards arena of business studies. Studies often question the applicability of its existence and practical applications. Starting from the base of unlearning this paper attempts to enfolds the multi-foci perspectives associated with unlearning. Aiming to analyse the construct, this paper provides an insight to definitional notions, account of existing stream of work, its unit of analysis at individual and organizational level and finally discussion of routines structured on unlearning perspective. Design/methodology/approach – A systematic analysis and review is proposed in order to study streams of literature existing on phenomenon existing on unlearning. This systematic review will help in stating various definitional notions of unlearning, identifying the theoretical lenses applied, processes underlying the unlearning mechanism and extent of quantitative and qualitative studies carried out. Originality/value – As the study is conceptual in its nature, therefore it aims to contribute towards identifying and enhancing the literature of unlearningby identifying gaps and future avenues. Enlightening the applicability of unlearning in multiple sectors it enhances its dimensionality. Practical implications – Study can be helpful for managers and organizations, as unlearning is rooting from change management, which would provide new revelations for organization as useful tools. Review provides insights to areas which can be useful for future studies.